2011
DOI: 10.1007/s11255-011-9928-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive performance of eGFR equations in South Africans of African and Indian ancestry compared with 99mTc-DTPA imaging

Abstract: MDRD-eGFR calculated without the African-American correction factor improved GFR prediction in African CKD patients and using the MDRD correction factor of 1.0 in Indian patients as in Caucasians may be inappropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 23 publications
3
27
1
Order By: Relevance
“…We calculated eGFR using the following equations: MDRD: eGFR (mL/min/1.73 m 2 ) = 175 × (serum creatinine (Scr) (µmol/L)/88.4) −1.154 × (Age) −0.203 (× 0.742 if female) [31]; CKD-EPI: eGFR (mL/min/1.73 m 2 ) = 144 × (0.993) age × ((Scr (µmol/L)/88.4)/0.7) −0.329 (if female and Scr ≤62 µmol/L) or ((Scr (µmol/L)/88.4)/0.7) −1.209 (if female and Scr >62 µmol/L) or ((Scr (µmol/L)/88.4)/0.9) −0.411 (if male and Scr ≤80 µmol/L) or ((Scr (µmol/L)/88.4)/0.9) −1.209 (if male and Scr >80 µmol/L) [32]; and Cockcroft-Gault: eGFR (mL/min) = ((140-age) × weight × 1.228)/Scr (μmol/L) (× 0.85 if female) [33]. Although the MDRD and CKD-EPI equations include a factor for Black race, we did not adjust eGFR for race in this study for the following reasons: (i) the equations were derived in African American patients not Southern African patients [31,32] and South African studies have found that eGFR calculated without the race factor is more accurate when compared to measured GFR for both the MDRD [34,35] and CKD-EPI equations [23,24]; (ii) the study sites do not routinely collect race data. Weights were not always recorded on the same dates as creatinine concentrations, so we matched weights to creatinine concentrations to calculate Cockcroft-Gault eGFR.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated eGFR using the following equations: MDRD: eGFR (mL/min/1.73 m 2 ) = 175 × (serum creatinine (Scr) (µmol/L)/88.4) −1.154 × (Age) −0.203 (× 0.742 if female) [31]; CKD-EPI: eGFR (mL/min/1.73 m 2 ) = 144 × (0.993) age × ((Scr (µmol/L)/88.4)/0.7) −0.329 (if female and Scr ≤62 µmol/L) or ((Scr (µmol/L)/88.4)/0.7) −1.209 (if female and Scr >62 µmol/L) or ((Scr (µmol/L)/88.4)/0.9) −0.411 (if male and Scr ≤80 µmol/L) or ((Scr (µmol/L)/88.4)/0.9) −1.209 (if male and Scr >80 µmol/L) [32]; and Cockcroft-Gault: eGFR (mL/min) = ((140-age) × weight × 1.228)/Scr (μmol/L) (× 0.85 if female) [33]. Although the MDRD and CKD-EPI equations include a factor for Black race, we did not adjust eGFR for race in this study for the following reasons: (i) the equations were derived in African American patients not Southern African patients [31,32] and South African studies have found that eGFR calculated without the race factor is more accurate when compared to measured GFR for both the MDRD [34,35] and CKD-EPI equations [23,24]; (ii) the study sites do not routinely collect race data. Weights were not always recorded on the same dates as creatinine concentrations, so we matched weights to creatinine concentrations to calculate Cockcroft-Gault eGFR.…”
Section: Methodsmentioning
confidence: 99%
“…Van Deventer et al [22] reported better performance of the MDRD equation in South Africans of African origin when the correction factor for black ethnicity was not used. Madala et al [23] also concluded that the MDRD equation should be used without the correction factor, and suggested that a new correction factor, or a new equation, is needed for South Africans of Indian origin.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the participants in this study will be of mixed ethnicity. It would also be very useful to have the data from the studies by Van Deventer et al [22] and Madala et al [23] re-analysed to include the CKD-EPI equation. A second issue is related to our recruitment methods.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst GFR-estimating equations have been validated in African-Caribbean communities from North America [29] and endemic Asian populations [30-35] there is no independent validation in British African-Caribbean populations; and no data at all amongst people originating from India, Pakistan, Sri Lanka and Bangladesh). There is some evidence that the black ethnicity coefficients in GFR estimating equations developed for use amongst African-Americans may not be transferable to other populations of African ancestry [36,37]. …”
Section: Introductionmentioning
confidence: 99%